Field applicable detection of hepatitis B virus using internal controlled duplex recombinase‐aided amplification assay and lateral flow dipstick assay. Issue 12 (1st April 2020) - Bai, Xueding; Ma, Xuejun; Li, Minghui; Li, Xinna; Fan, Guohao; Zhang, Ruiqing; Wang, Ruihuan; Duan, Qingxia; Shen, Xinxin; Xie, Yao; Rong, Xiuge
Abstract: Hepatitis B virus (HBV) is a widespread blood‐borne pathogen associated with the complication of liver cirrhosis and hepatocellular carcinoma, particularly in south‐east Asian and African countries where HBV is highly endemic and the budget and resources are limited. Therefore, simple, rapid, and portable field detection methods are crucial to efficiently control HBV infection. In this study, using heat‐treated DNA, we developed two‐field applicable detection assays for HBV based on recombinase‐aided amplification (RAA). One was an internal controlled duplex RAA assay using a portable real‐time fluorescence detection device, another was an instrument‐free visual observation assay using lateral flow dipsticks. The entire experimental time was greatly shortened to less than 40 minutes at 39.0°C. The sensitivities, specificities, and clinical performance of both assays were evaluated. Compared with quantitative polymerase chain reaction assay as a reference, our results demonstrated that the two RAA‐based assay obtained 97.18% and 95.77% of sensitivity, respectively, and the specificity was 100%, by testing a total of 157 serum samples with HBsAg positive. We conclude that the advantages of rapidity, simplicity, portability, and visualization of proposed two assays make them great potentials in point‐of‐care testing of HBV infection by untrained people in resource‐limited situations. Research Highlights: HBV is a widespread blood‐borne pathogen associated with the complication of liver cirrhosis and hepatocellular carcinoma. We present a rapid RAA assay to detect HBV without DNA extraction. This assay can be performed in a single closed tube at 39℃ within 30 min. The sensitivity of the internally controlled RAA assay was 10 2 IU/ml. The introduction of IAC effectively reduced the occurrence of false negatives.